Non-invasive management of maxillary labial undercuts in complete removable dentures using soft liners in a patient with maxillary labial undercut: a case report - Zakiyah, Nida; Hanifah, Niken Fibrian Nuriati; Waskitho, Arief; dalanon, junhel (Padjadjaran Journal of Dentistry, 2025)
Introduction: Individuals who have lost all their teeth should promptly receive rehabilitative treatment with complete dentures to restore lost functions and structures. Bone protrusions or undercuts are factors that can interfere with prosthetic function. A common treatment for undercuts is their removal through alveolectomy surgery; however, the complexity of the procedure could lead to relatively long-time wound healing and post operative discomfort. This report aimed to discuss the management of a fully edentulous patient with complete dentures who presented with a maxillary labial undercut with alternative treatment beside surgery using soft liners in a patient who has maxillary labial undercut. Case report: A 54-year-old woman visited the Dental Hospital Universitas Muhammadiyah Yogyakarta, complaining of discomfort due to her dentures being loose, particularly in the lower jaw. She had experienced denture looseness since the first time she wore the complete denture. The patient initially used denture adhesive to prevent the denture from dislodging, but it was now used very rarely. A labial undercut was observed in the anterior region of the maxilla. The patient underwent complete removable denture treatment using soft liners to cover the area left by labial undercuts. Discussion: The elastic properties of the soft liner can alleviate pressure on protruding bones, resulting in greater comfort when using complete dentures.  Conclusion: The use of soft liners serves as an alternative to pre-prosthetics surgery in cases of labial undercut. This approach is considered more comfortable for patients, as it is elastic and does not put pressure on soft tissue.